DIALEKTIKA ANTARA HUSHULI, HUDHURI, BAYANI, IRFANI DAN BURHANI: (Term Epistemologi Filsafat Islam Modern) - Almutawallid (Prodi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Filsafat UIN Alauddin Makassar, 2023)
This article examines the dialectic between various schools of thought in Islamic philosophy: Hushuli, Huduri, Bayani, Irfani, and Burhani, employing a qualitative philosophical approach through library research. The primary focus is twofold: First, the debate between Hushuli and Huduri, centered on whether knowledge is correspondence-based (knowledge about—external), or immanent (knowledge by presence—internal). Second, the debate between Bayani, Burhani, and Irfani, focusing on how knowledge is produced, its object, and its source. The research reveals that, firstly, the Hushuli school posits knowledge as correspondence-based, requiring an exchange of information between subject and object—an external process. Conversely, the Huduri school argues for immanent knowledge, asserting that knowledge is inherently present, directly experienced reality, emphasizing personal experience, reason, reflection, and contemplation—an internal process. Secondly, regarding Bayani, Burhani, and Irfani, the research shows that Bayani views texts as the object of knowledge and truth, with reason as its instrument. Burhani, on the other hand, considers the universe/reality as its object, utilizing rationality and empirical observation (laboratory methods) as its primary tools. Irfani, however, posits the God-knowing soul as the object of knowledge, arguing that rationality and raw texts are insufficient; intuition (kashf) and inner reflection are necessary. Knowledge, in this perspective, is attained through direct divine illumination.